Communication Under Pressure: A Quasi-Experimental Study to Assess the Impact of a Structured Curriculum on Skilled Communication to Promote a Healthy Work Environment. Issue 5 (September 2019) - Jones, Lindsay; Cline, Genieveve J.; Battick, Kentlee; Burger, Kristina J.; Amankwah, Ernest K.
Abstract : Effective communication in health care is a mainstay of patient safety and staff perception of a healthy work environment. A quasi-experimental study was conducted to assess the impact of a course on staff perceptions of communication. A Wilcoxon signed-ranks test indicated a statistically significant difference between pre and post scores for the self-assessment component of the Heathy Work Environment Instrument ( p = .0005); coworker assessments revealed borderline statistical significance ( p = .056).